Evaluasi Akuntabilitas dan Pengawasan Internal Program Budidaya Ikan Lele Berdasarkan Siklus Akuntansi Sektor Publik pada BUMDes Ajoeng Jaya - Ana Rosalia; Dea Azzahrotu Dinji; Adinda Dwi Permatasari; Siti Risviana Nuruil Janah; Afrijal Ramadani; Septia Ningsih; Prillinaya Yudhistira; Oryza Ardhiarisca (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to evaluate the effectiveness of the implementation of the public sector accounting cycle in the planning, implementation, administration, and evaluation of catfish cultivation programs run by BUMDes Ajoeng Jaya as part of the village food security program. The focus of the research departs from the need to ensure that each stage of the management of the BUMDes program runs according to the principles of public accountability, considering that BUMDes is a strategic entity in the management of village resources to improve the welfare of the community. This study uses a qualitative descriptive approach through field observation, in-depth interviews with the management of BUMDes Ajoeng Jaya, and a review of documentation related to catfish farming program activities and financial records. This approach allows researchers to gain a comprehensive understanding of the accounting practices applied as well as the various obstacles that arise during the implementation of food security programs. The results of the study show that the catfish cultivation program has failed due to weak internal supervision, the absence of SOPs, lack of financial recording and reporting, and lack of technical competence of managers. The implementation of the public sector accounting cycle has not been running optimally so that it is not able to support effective control and evaluation of programs. In addition, crop failures are exacerbated by theft by internal parties and the absence of a structured monitoring system throughout the program, which indicates weak governance and internal control. This study has limitations in the form of a small number of informants and a lack of formal documents, so the analysis—especially the financial aspect—cannot be generalized widely. Nevertheless, this study contributes by integrating the evaluation of food security programs through the implementation of the public sector accounting cycle and offering recommendations to improve the accountability, transparency, and sustainability of BUMDes programs.